2016
DOI: 10.1101/086587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A network-based approach to eQTL interpretation and SNP functional characterization

Abstract: 1 Summary Expression quantitative trait locus (eQTL) analysis associates genotype with gene expression, but most eQTL studies only include cis-acting variants and generally examine a single tissue. We used data from 13 tissues obtained by the Genotype-Tissue Expression (GTEx) project v6.0 and, in each tissue, identified both cis-and trans-eQTLs. For each tissue, we represented significant associations between single nucleotide polymorphisms (SNPs) and genes as edges in a bipartite network. These networks are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This study demonstrated that eQTL communities are comprised of functionally related sets of variants, including GWAS SNPs, in a tissue-specific manner. In addition, for diseases such as chronic obstructive pulmonary disease, SNPs significantly associated with chronic obstructive pulmonary disease risk were enriched within eQTL intermediate nodes (Fagny et al, 2016). This is consistent with results suggesting that the genetic component of many disease phenotypes are combinations of GWAS SNPs of small to intermediate effect sizes, in contrast to causal pharmacogenomic SNPs identified from GWAS that exhibit moderate to large effects sizes (Higgins et al, 2015a).…”
Section: B the Functional Topology Of The Three-dimensional Spatial supporting
confidence: 86%
See 2 more Smart Citations
“…This study demonstrated that eQTL communities are comprised of functionally related sets of variants, including GWAS SNPs, in a tissue-specific manner. In addition, for diseases such as chronic obstructive pulmonary disease, SNPs significantly associated with chronic obstructive pulmonary disease risk were enriched within eQTL intermediate nodes (Fagny et al, 2016). This is consistent with results suggesting that the genetic component of many disease phenotypes are combinations of GWAS SNPs of small to intermediate effect sizes, in contrast to causal pharmacogenomic SNPs identified from GWAS that exhibit moderate to large effects sizes (Higgins et al, 2015a).…”
Section: B the Functional Topology Of The Three-dimensional Spatial supporting
confidence: 86%
“…Tissue-specific, regulatory cis-and trans-interacting community-based networks have been characterized by combining disease SNPs from GWAS with eQTL data (Fagny et al, 2016). To detect regulatory communities, cis-and trans-eQTLs from 13 human tissues were mapped using bipartite graphs, in which significant eQTLs were revealed as edges of a bipartite network linking SNPs and gene nodes.…”
Section: B the Functional Topology Of The Three-dimensional Spatial mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that organization of paternal compartmentalization is likely inherited from the sperm [75]. The organization of loops, TADs, and compartments is significant because it infers which regions are more active and perhaps more prone to mutations [7]. On a more localized level, a separate study used a modified sciATAC-SEQ approach called SCI-seq was demonstrated on 16,000 single cells from different cancer types.…”
Section: Exemplary Applicationsmentioning
confidence: 99%
“…However, as mutations accumulate over time, they increase genetic variations and the likelihood of developing a neoplasm. Communities of mutations, or alterations to driver genes, can lead to increases in proliferation, a higher frequency of errors in transcription and replication, and/or the enabling of apoptotic evasion [6,7]. Finally, recent studies indicate that metastases may also derive from early disseminated cancer cells [8].…”
Section: Introductionmentioning
confidence: 99%